Prevalence and diversity of antimicrobial resistant pathogens from medical and community wastewater in Dhaka City - Bulbuli, Naima Hasan; Awysharjaw, Rownak Showkat; Lohani, Tabassum (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.